Twitter as a Polarized Space for Civil Society Organizations (CSOs) in Turkey - Sema Akboğa; Engin Arık (İnsan & Toplum)
Research on the coverage of CSOs on social media and the use of social media by CSOs has been gaining momentum. To contribute to this line of research, this study investigates the coverage of civil society organizations (CSO) on Twitter in Turkey by focusing on the most frequently mentioned organizations. It examines the characteristics of these CSOs as well as the effect that social and political developments in Turkey have on their coverage on Twitter. e data were collected from Twitter for the period between August 18, 2019 and September 17, 2019. We found that CSOs were not equally mentioned on Twitter; a total of 29,387 tweets mentioned 4,941 different CSOs, representing only 3.98% of all CSOs in Turkey. We also found that, with a few exceptions, tweets were not equally distributed in number across the CSOs or over time. Furthermore, the content of the tweets about the most frequently mentioned CSOs was strongly related to the political developments in Turkey, thereby reecting the politically polarized views about the organizations in Turkey. erefore, we concluded that ideological divisions in politically polarized countries such as Turkey shape the coverage of CSOs on Twitter.